Peran mindfulness dalam meningkatkan konsentrasi belajar siswa Madrasah Ibtidaiyah - Hamid, Ahmad Dhani (Maliki Interdisciplinary Journal, 2026)
Learning concentration is a crucial factor in students’ academic success, particularly at the Islamic elementary school (Madrasah Ibtidaiyah) level. However, low learning focus is often a common issue due to internal and external distractions. This study aims to examine the role of mindfulness in improving students’ learning concentration. The method used is a literature review by analyzing various sources related to mindfulness and learning concentration. The results indicate that mindfulness helps students enhance self-awareness, manage emotions, and focus their attention on learning activities. The implementation of mindfulness in the classroom can be carried out through conscious breathing techniques, simple meditation, and attention training. Therefore, mindfulness has the potential to be an effective strategy to improve the quality of learning in Madrasah Ibtidaiyah.